Homicide by Multiple Fatal Methods: A Study From South Delhi, India - Behera, Chittaranjan (Journal of interpersonal violence, 2021)
Homicide studies traditionally analyze the prevalence and patterns of homicide by exploring the age and sex of victims, the relationship between victims and perpetrators, and the cause of death. Use of a combination of more than one homicidal method was also found in various studies. Some of them found females as more common victims of multiple methods, whereas the others found males. Combination of methods commonly involved were sharp trauma, blunt trauma, and strangulation. This study was undertaken to know the pattern of homicide by multiple fatal methods at South Delhi. We have analyzed retrospective data of homicidal deaths in which multiple different fatal methods were used. We have also analyzed the number of perpetrators involved in those scenarios. The cases were autopsied at All India Institute of Medical Sciences, New Delhi during the 20-year period from January 1996 and December 2015. There were 187 such reported cases where multiple methods were used for homicide, constituting 13.6% of all homicide deaths autopsied at the department. Multiple methods were used more commonly against female victims. Methods used in cases of male victims were the combination of head injury and stabbing in the chest/abdomen, followed by strangulation with smothering, whereas in cases of female victims, it was a combination of ligature strangulation and smothering which was most common, followed by the combination of smothering with throttling. Gunshot with stabbing was found to be a rare combination. A single perpetrator mostly used various asphyxial methods in combination or head injury with other methods such as stabbing and asphyxiation against male as well as female victims. Other combinations of methods, especially sharp weapon injury with blunt weapon injury or gunshot injury, suggest the involvement of more than one perpetrator.